2013
DOI: 10.7470/jkst.2013.31.3.033
|View full text |Cite
|
Sign up to set email alerts
|

Diversion Rate Estimation Model for Unexperienced Transportation Mode by Considering Maximum Willingness-to-pay: A Case Study of Personal Rapid Transit

Abstract: Personal Rapid Transit(PRT) has emerged as a promising transportation mode for transit-oriented sustainable communities. In this study, an alternative design of questionnaire survey is proposed in order to capture traveler's perception of an unexperienced transportation mode. This study aims at predicting the mode choice diversion behavior of potential PRT users who do not have experience of using it previously, considering their willingness-to-pay. The proposed model was applied to predict an aggregate foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…In the past decade, other research has been conducted to predict changes in the mode choice behavior of respondents by checking their willingness to pay (WTP) [19,20]. One of the most comprehensive research studies evaluating ATN systems, called Evaluation and Demonstration of Innovative City Transport (EDICT), showed that not only was the concept of ATN welcomed by the public in all the cities that participated in the project, but also people would be willing to pay a fare of two to three times the amount set out in the project survey because this system ofered additional benefts compared to conventional public transport modes [13].…”
Section: Automated Transit Network (Atn)mentioning
confidence: 99%
“…In the past decade, other research has been conducted to predict changes in the mode choice behavior of respondents by checking their willingness to pay (WTP) [19,20]. One of the most comprehensive research studies evaluating ATN systems, called Evaluation and Demonstration of Innovative City Transport (EDICT), showed that not only was the concept of ATN welcomed by the public in all the cities that participated in the project, but also people would be willing to pay a fare of two to three times the amount set out in the project survey because this system ofered additional benefts compared to conventional public transport modes [13].…”
Section: Automated Transit Network (Atn)mentioning
confidence: 99%